Howard White Oral History Interview - (:unkn) unknown (My University, 2012)
Howard White has a wealth of information from watching his grandfather Herman D. White, Eau Claire's "Mr. Baseball". The interview with Mr. White took place on March 12, 2012 at 9:00 a.m. The questions that were covered were: When you think of Eau Claire baseball, what memories come to mind? Were any other members of your family involved in baseball as much as your grandfather? How were they involved? Did your grandfather ever tell any interesting stories of famous players that played for the Eau Claire Bears? And what were some of the best stories he ever told you? Did your grandfather ever mention any controversies on the signing of black players to the Eau Claire Bears? Do you know how your grandfather reacted to the folding of the Northern League? Some of the responses that Mr. White had included were the conditions of travel during the prime years of the Northern League. He had spoken about how the Eau Claire team had traveled in hearses that were remodeled for the baseball team to use to travel throughout the North. Those travels had included as well constant repair of the vehicles, especially changing flat tires due to the travel on poorly graveled roads that were common during that time. Another aspect that Mr. White had focused on was of how baseball has always been an essential aspect of Eau Claire. This is because he strongly believes that baseball has always been a pasttime that families could enjoy together, from being part of the team to watching a baseball game underneath the lights at Carson Park Stadium. At this point, he does talk about some of the feelings he does have about the University not having a baseball team.